Accurate buckling analysis for shear deformable FGM cylindrical shells under axial compression and thermal loads. (May 2015) - Sun, Jiabin; Xu, Xinsheng; Lim, C.W.; Qiao, Weiyu
Abstract: Based on the Reddy's high-order shear deformation theory, buckling behaviors of the FGM cylindrical shells subjected to an axial compression in thermal environment are investigated analytically. Considering the temperature-dependent FGMs properties, the constituent distribution across the shell thickness is assumed to follow the volume fraction rule of mixture. Through the variational principle, basic equations are derived for shear deformable FGM cylindrical shell with the initial geometric imperfection. Method of separation of variables and Galerkin's solving process are employed in dealing with the stability governing equations of perfect and imperfect shells, respectively. By changing the boundary conditions, material types, composition distributions, thermal load and temperature fields, the effect of the transverse shear deformation is evaluated by comparing with the results of the classical Donnell's theory. Meanwhile, imperfection sensitivity for buckling of the shear deformable FGM cylindrical shell is discussed in detail.